2020
DOI: 10.1007/978-3-030-59713-9_55
|View full text |Cite
|
Sign up to set email alerts
|

Peri-Diagnostic Decision Support Through Cost-Efficient Feature Acquisition at Test-Time

Abstract: Computer-aided diagnosis (CADx) algorithms in medicine provide patient-specific decision support for physicians. These algorithms are usually applied after full acquisition of high-dimensional multimodal examination data, and often assume feature-completeness. This, however, is rarely the case due to examination costs, invasiveness, or a lack of indication. A sub-problem in CADx, which to our knowledge has received very little attention among the CADx community so far, is to guide the physician during the ent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
(32 reference statements)
0
4
0
Order By: Relevance
“… Mahurkar & Gaikwad (2017) exploit artificial neural networks in conjunction with K-Means to normalize raw data for hypo- and hyperthyroidism. In Vivar et al (2020) , a guiding computer-aided diagnosis system, using a neural network with a dropout at the input layer, and integrated gradients of the trained network at test-time to attribute feature importance dynamically, is proposed. The technique is applied also to the UCI thyroid dataset to detect both hypo- and hyperthyroidism.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Mahurkar & Gaikwad (2017) exploit artificial neural networks in conjunction with K-Means to normalize raw data for hypo- and hyperthyroidism. In Vivar et al (2020) , a guiding computer-aided diagnosis system, using a neural network with a dropout at the input layer, and integrated gradients of the trained network at test-time to attribute feature importance dynamically, is proposed. The technique is applied also to the UCI thyroid dataset to detect both hypo- and hyperthyroidism.…”
Section: Resultsmentioning
confidence: 99%
“…Looking at the public datasets, we observed that the most used dataset is the UCI one ( https://archive.ics.uci.edu/ml/datasets/Thyroid+Disease ), exploited 27 times ( Duggal & Shukla, 2020 ; Shahid et al, 2019 ; Pan et al, 2016 ; Pavya & Srinivasan, 2017 ; Mahurkar & Gaikwad, 2017 ; Ahmed & Soomrani, 2016 ; Tyagi, Mehra & Saxena, 2018 ; Kumar, 2020 ; Pasha & Mohamed, 2020 ; Shen et al, 2016 ; Bentaiba-Lagrid et al, 2020 ; Raisinghani et al, 2019 ; Vivar et al, 2020 ; Li et al, 2019b ; Ma et al, 2018 ; Kour, Manhas & Sharma, 2020 ; Khan, 2021 ; Priyadharsini & Sasikala, 2022 ; Peya, Chumki & Zaman, 2021 ; Chaubey et al, 2021 ; Hosseinzadeh et al, 2021 ; Juneja, 2022 ; Kishor & Chakraborty, 2021 ; Islam et al, 2022 ; Saktheeswari & Balasubramanian, 2021 ; Chandel et al, 2016 ; Priya & Manavalan, 2018 ). The UCI dataset is characterized by 7,200 instances and 21 categorical and real attributes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, we compare several linear, non-linear and neural-network based ML algorithms, along with a novel graph deep learning method that we recently proposed (6,12,13). Following insights from multiple classification experiments for diagnostic decision support in our research over the last few years (4,6,13,14), we also provide a multi-faceted analysis of algorithm outcomes, including an examination of class imbalance, multiple classification metrics, patient feature distributions, and feature importances as rated by the classifiers. To alleviate the implementation burden for multi-algorithm comparison and multivariate evaluation, we provide base-ml as an open-source tool 1 to the vestibular research community, as a starting point for further studies in this direction.…”
Section: Introductionmentioning
confidence: 99%